Common Methods to Treat Addiction in Treatment- Rehabilitation Centers in Tehran - H Sharifi; R Kharaghani; S Sigari; H Emami; M Sadr; MR Masjedi (Tehran University of Medical Sciences, 2012)
Background: This study was to determine common methods to treat addiction used by patients checked into Outpatient Treatment and Rehabilitation Clinics in Tehran. Methods: The study was conducted in Social Security affiliated outpatient clinics including three governmental and several private centers in 22 districts of Tehran. Demographic data, personal information, social characteristics and information regarding prevention, treatment, and follow-up records of 1,372 patients were obtained and analyzed. Results: A majority of cases referring to the treatment centers were male (95.2%).  Patients were 14 to 75 yr (mean 35.48 ± 10.57 yr); 61.7% were married and lived in rented homes in the city; 938/1372 (68.4%) had at least one previous attempt failure when seeking re-treatment. A majority of them (77.8%) had a history of 1 to 4 quit attempts; a number 63.1% had an abstinence period of 1 week to 6 months. Conclusion: The majority of our understudy subjects had a history of previous attempts to treat their addiction with a maximum abstinence period of 6 months.